English for professionals and graduate employability: exploring Malaysian college ESL students' perceptions of creating digital video CV task in 4.0 classroom - Darmi, Ramiaida; Mat Saad, Noor Saazai; Ab. Wahab, Nursyuhada'; Puteh-Behak, Fariza; Darmi, Ramiza; Idrus, Mohd Mushafar (Penerbit Universiti Malaysia Perlis, 2020)
Unemployability among graduates has become one of the greatest concerns of the education ministry in Malaysia. One reason is that graduates lack the potential skills listed by the Malaysian industries. This study focuses on one of the hard skills listed, curriculum vitae (CV) writing. The study proposed a shift from the conventional written CV to a digital video CV. Such proposal could support the ministry’s shifts in embedding technology-based tasks into the 4.0 classroom. Using a heutagogical approach in the English for Professionals course, learners were required to prepare a 2-minute digital video CV, which was then posted in Padlet. Through the task, the researcher aimed at exploring learners’ perceptions of the learning task of creating a digital video CV and gather their perceptions of the conduciveness of creating the digital video CV for future employment. By employing a quantitative approach, learners were required to answer an online 5-point Likert-type survey, which was analysed using Microsoft Excel. The findings showed that most of the participants agreed that the task was not only fun, interesting, and enjoyable, but also challenging, creativity-driven, and knowledge-seeking. Concerning the workforce, majority of the participants felt that the task made them work-ready, exposed them to multiple online tools, became more independent and critical as they employed different higher-order thinking skills when completing the task. Future research should apply the heutagogical approach so that learners are more independent towards their learning and focus on the hard and/or soft skills required in graduates, making them more marketable.